Lower DWI-ASPECTS Score in Cortical Regions Predicts Unfavorable Outcome after Successful Thrombectomy - Hori, Satoshi; Furudate, Ryutaro; Kumagai, Izumi; Aoyagi, Chikashi; Hirota, Nobuo; Yamamoto, Tetsuya (Indian Journal of Neurosurgery, 2025)
Background Mechanical thrombectomy has been established as an effective treatment for acute ischemic stroke (AIS) caused by large vessel occlusion (LVO). However, the factors predicting poor outcomes despite successful reperfusion after thrombectomy remain unclear.Methods This study included 50 patients who achieved successful reperfusion after mechanical thrombectomy between January 2014 and March 2021. The diffusion-weighted imaging (DWI) Alberta Stroke Program Early Computed Tomography Score (ASPECTS) was stratified into deep (dDWI-ASPECTS) and cortical (cDWI-ASPECTS) components. Baseline clinical characteristics and procedural factors were statistically analyzed to identify variables associated with unfavorable outcomes, defined as a modified Rankin scale score of 3 to 6.Results Seventeen patients (34%) achieved favorable outcomes, while 33 (66%) had unfavorable outcomes. The cDWI-ASPECTS were significantly higher in the favorable outcome group compared with the unfavorable outcome group (p = 0.01), whereas no significant differences were observed in the dDWI-ASPECTS. Multivariate analysis identified older age (p < 0.01; odds ratio [OR]: 1.15; 95% confidence interval [CI]: 1.04–1.27), lower baseline cDWI-ASPECTS (p < 0.01; OR: 2.71; 95% CI: 1.30–5.56), and higher baseline National Institutes of Health Stroke Scale (NIHSS) scores (p = 0.03; OR: 1.21; 95% CI: 1.02–1.44) as independent predictors of unfavorable outcomes.Conclusion A lower baseline cDWI-ASPECTS score serves as a predictive factor for unfavorable outcomes following successful thrombectomy, particularly in older AIS-LVO patients with higher baseline NIHSS scores.
Keywords: DWI-ASPECTS; thrombectomy; acute ischemic stroke; large vessel occlusion